As informações sobre ativos intangíveis nos relatórios da Vale- 2013: um estudo exploratório - Oliveira, Ivone Alves do Vale de (2015)
Qualitative / Quantitative research that aimed to identify contributions for information on intangible assets in 2013 reports of Vale Company. The methodology adopted was an exploratory study with a qualitative / quantitative approach. The quantitative analysis was done through the AntConc software. Qualitative analysis was the methodological approach applied for data analysis. The results indicate no explicit information of intangible assets in the company's reports. It was possible to identify unusual terminology information of intangible assets related to the knowledge capital.